Substance use screening and rates of treatment referral among justice-involved youth. (November 2021) - Yurasek, Ali M.; Kemp, Kathleen; Otero, Jessica; Tolou-Shams, Marina
Highlights: Approximately half of youth positively screened for problematic substance use. Despite positive substance use screens, treatment referral was low. Alcohol and cannabis co-users had greater odds of positively screening on both tools. The CRAFFT (vs. MAYSI-2) may be more accurate at identifying problem cannabis use. Accurate identification of substance use treatment needs for this population is needed. Abstract: Background: Justice-involved youth report high rates of substance use and related problems that are associated with treatment needs; however, data on screening and linkage to treatment within the justice system is lacking. To further inform the juvenile justice behavioral health cascade of care, this study examined factors associated with identified problematic substance use and treatment referral using two screening tools. Method: As part of a family court intake process, 348 justice-involved youth received two screening measures, the MAYSI-2 alcohol/drug use subscale and the CRAFFT. Both tools are designed to indicate early warning signs of substance use problems and signal referral for further clinical evaluation or treatment. Chart review analysis examined whether demographic variables (sex & race), severity of use, and type of substance used were associated with positive screens on either or both measures and subsequent treatment referral. Results: Half (51.2%) of youth were identified as having problematic substance use (a positive screen) on at least one of the screeners. Overall, 38.5% positively screened on the CRAFFT with only 0.3% positively screening on just the MAYSI-2 alcohol/drug scale. Cannabis only users were less likely to positively screen on the MAYSI-2 compared to youth who reported use of both alcohol and cannabis. Positively screening on one versus both screeners was not associated with referral, yet many (28%) who positively screened were not referred for services. Conclusions: The CRAFFT may be more accurate at identifying youth specifically at risk for problematic cannabis use compared to the MAYSI-2 alcohol/drug subscale. Regardless of tool used, treatment referral was low, highlighting the need for accurate identification of treatment needs of substance-using, justice-involved youth. Interventions to facilitate referrals for youth with problematic substance use are needed.